The changing character of war - Strachan, Hew.; Scheipers, Sibylle (Oxford : Oxford University Press, 2011)
'The Changing Character of War' unites scholars from the disciplines of history, politics, law and philosophy to ask in what ways the character of war today has changed from war in the past and how the wars of today differ from each other.
Includes bibliographical references and index.
Description based on print version record.
Keywords: War; War (Philosophy)